NATURAL HISTORY AND BIOGEOGRAPHY OF THE AMPHIBIANS AND REPTILES OF KIBALE NATIONAL PARK, UGANDA - Vonesh, James (Contemporary Herpetology, 2001)
This study lists the amphibian and reptile species of Kibale National Park, Uganda, and discusses the natural history and biogeography of this unique herpetofauna. This herpetofaunal inventory was compiled based upon literature records and collections made during 17 mo fieldwork between 1995 and 1997, and includes 28 anuran, 15 lizard, and 32 snake species. Faunal comparisons with seven other tropical African forests show a high degree similarity between the Kibale herpetofauna and those of central and West Africa.